LAKON BANJARAN BHISMA VERSI KI NARTOSABDO - Timbul Subagya (LP2M ISBI Bandung, 2016)
The aim of this article is to find out the position ofLakon Banjaran Bhisma in the field ofpuppetry and the existence of Bhisma according to Indian and Java tradition, especially Surakarta puppetry tradition. The approach used is descriptive method to describe mythology of Bhisma stories both in Indian and Wagang Surakarta tradition, The result shows that lakonBanjaran Bhisma is lakon model ever performed by Ki Narto Sabdo. This Lakon tells about the life of Bhisma since his birth until his death in Bharatadha war, the great war ofPandawa against Korawa. Based on Bhisma stories in lakon Banjaran Bhisma above, it is concluded that KiNartosabdo in presenting this lakon refers to the sources of lakoninSurakartapuppetry tradition.Keywords : Bhisma, lakon, puppetry, Surakarta.